ANALYSIS OF THE CANVAS MODEL BUSINESS FOR FISH FARMING IN SANGRIANG FARM, TUATUNU SUB-DISTRICT, GERUNGGANG SUB-DISTRICT, PANGKALPINANG CITY - Soleha Soleha; Endang Bidayani; Ardiansyah Kurniawan (Journal of Fish Health, 2022)
The fish farming business in Pangkalpinang City is growing along with the increasing demand for aquaculture products. Sangriang Farm is a fish farming business engaged in the hatchery and rearing of Gurame ( Osphronemus goramy ), Catfish ( pangasius sp .), Goldfish ( Cyprinus carpio ), Tilapia ( Oreochromis niloticus ), and Catfish ( Clarias sp .). This study aims to analyze existing business models and recommend new business models through the Business Model Canvas (BMC). The research method used in this study is a survey method with a case study technique. Analysis of existing conditions reinforced by SWOT analysis resulted in BMC improvements in Channels elements (use of social media, product labels, and packaging), Key Resources (additional human resources, capital, and intensification of cultivation technology), Customer Segments (target consumers of semi-finished processed products and restaurant suppliers), and Revenue Streams (bookkeeping management and product diversification). Implementing the recommendations is expected to increase the business capacity of Sangriang Farm.